# Divide and solve dt dt 4 8t 2t to get y 256x one

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: r × r = (ac/w3 ) sin(s/w)i − (ac/w3 ) cos(s/w)j + (a2 /w3 )k, (r × r ) · r = a2 c/w6 , r (s) = a/w2 , so τ = c/w2 and B = (c/w) sin(s/w)i − (c/w) cos(s/w)j + (a/w)k dT ds dT = = (κN)s = κs N, dt ds dt dN ds dN = = (−κT + τ B)s = −κs T + τ s B. N= dt ds dt 66. (a) T = (b) r (t) = s so r (t) = s T and r (t) = s T + s T = s T + s (κs N) = s T + κ(s )2 N. (c) r (t) = s T + s T + κ(s )2 N + [2κs s + κ (s )2 ]N = s (κs N) + s T + κ(s )2 (−κs T + τ s B) + [2κs s + κ (s )2 ]N = [s − κ2 (s )3 ]T + [3κs s + κ (s )2 ]N + κτ (s )3 B. (d) r (t) × r (t) = s s T × T + κ(s )3 T × N = κ(s )3 B, [r (t) × r (t)] · r (t) = κ2 τ (s )6 so τ= [r (t) × r (t)] · r (t) [r (t) × r (t)] · r (t) = 2 (s )6 κ r (t) × r (t) 2 67. r = 2i + 2tj + t2 k, r = 2j + 2tk, r = 2k, r × r = 2t2 i − 4tj + 4k, r × r = 2(t2 + 2), τ = 8/[2(t2 + 2)]2 = 2/(t2 + 2)2 68. r = −a sin ti + a cos tj + bk, r = −a cos ti − a sin tj, r r × r = ab sin ti − ab cos tj + a k, r × r 2 = = a sin ti − a cos tj, a2 (a2 + b2 ), τ = a2 b/[a2 (a2 + b2 )] = b/(a2 + b2 ) √ √ √ 69. r = et i − e−t j + 2k, r = et i + e−t j, r = et i − e−t j, r × r = − 2e−t i + 2et j + 2k, √ √ √ r × r = 2(et + e−t ), τ = (−2 2)/[2(et + e−t )2 ] = − 2/(et + e−t )2 70. r = (1 − cos t)i + sin tj + k, r = sin ti + cos tj, r = cos ti − sin tj, r × r = − cos ti + sin tj + (cos t − 1)k, r ×r = cos2 t + sin2 t + (cos t − 1)2 = 1 + 4 sin4 (t/2), τ = −1/[1 + 4 sin4 (t/2)] Exercise Set 14.6 512 EXERCISE SET 14.6 1. v(t) = −3 sin ti + 3 cos tj a(t) = −3 cos ti − 3 sin tj 9 sin2 t + 9 cos2 t = 3 √ r(π/3) = (3/2)i + (3 3/2)j √ v(π/3) = −(3 3/2)i + (3/2)j √ a(π/3) = −(3/2)i − (3 3/2)j 2. v(t) = i + 2tj a(t) = 2j v(t) = v(t) = √ 1 + 4t2 r(2) = 2i + 4j v(2) = i + 4j a(2) = 2j y y v = − 3√3i + 3 j 2 2 v = i + 4j 8 a = 2j (3 , 3 √ 3) 22 (2, 4) x 3 a=− 3 3√3 j i− 2 2 3. v(t) = et i − e−t j 4. v(t) = 4i − j −t t x 4 a(t) = e i + e j √ v(t) = e2t + e−2t a(t) = 0 r(0) = i + j r(1) = 6i v(0) = i − j v(1) = 4i − j a(0) = i + j a(1) = 0 v(t) = √ 17 y y a=i+j (6, 0) (1, 1) x x v = 4i − j a=0 v=i−j 5. v = i + tj + t2 k, a = j + 2tk; at t = 1, v = i + j + k, v = √ 3, a = j + 2k 6. r = (1 + 3t)i + (2 − 4t)j + (7 + t)k, v = 3i − 4j + k, √ a = 0; at t = 2, v = 3i − 4j + k, v = 26, a = 0 7. v = −2 sin ti + 2 cos tj + k, a = −2 cos ti − 2 sin tj; √ √ √ √ √ at t = π/4, v = − 2i + 2j + k, v = 5, a = − 2i − 2j 8. v = et (cos t + sin t)i + et (cos t − sin t)j + k, a = 2et cos ti − 2et sin tj; at t = π/2, v = eπ/2 i − eπ/2 j + k, v = (1 + 2eπ )1/2 , a = −2eπ/2 j 513 Chapter 14 9. (a) v = −aω sin ωti + bω cos ωtj, a = −aω 2 cos ωti − bω 2 sin ωtj = −ω 2 r (b) From Part (a), a = ω 2 r 10. (a) v = 16π cos πti − 8π sin 2πtj, a = −16π 2 sin πti − 16π 2 cos 2πtj; at t = 1, v = −16π i, v = 16π , a = −16π 2 j (b) x = 16 sin πt, y = 4 cos 2πt = 4 cos2 πt − 4 sin2 πt = 4 − 8 sin2 πt, y = 4 − x2 /32 (c) Both x(t) and y (t) are periodic and have period 2, so after 2 s the particle retraces its path. √ 11. v = (6/ t)i + (3/2)t1/2 j, v = 36/t + 9t/4, d v /dt = (−36/t2 + 9/4)/(2 36/t + 9t/4) = 0 √ if t = 4 which yields a minimum by the ﬁrst derivative test. The minimum speed is 3 2 when r = 24i + 8j. 12. v = (1 − 2t)i − 2tj, v = (1 − 2t)2 + 4t2 = √ 8t2 − 4t + 1, 8t − 2 d 1 v =√ which yields a minimum by the ﬁrst derivative test. The = 0 if t = dt 4 8t2 − 4t + 1 √ 1 3 i − j. minimum speed is 1/ 2 when the particle is at r = 16 16 13. (a) 6 0 3 8 (b) v = 3 cos 3ti + 6 sin 3tj, v = 9 cos2 3t + 36 sin2 3t = 3 1 + 3 sin2 3t; by inspection, maximum speed is 6 and minimum speed is 4 (d) d 9 sin 6t v= = 0 when t = 0, π/6, π/3, π/2, 2π/3; the maximum speed is 6 which dt 2 1 + 3 sin2 3t occurs ﬁrst when sin 3t = 1, t = π/6. 8 14. (a) 0 0 c (d) v = −6 sin 2ti + 2 cos 2tj + 4k, v = 36 sin2 2t + 4 cos2 2t + 16 = 2 8 sin2 t + 5; by inspec√ √ tion the maximum speed is 2 13 when t = π , the minimum speed is 2 5 when t = π/2. 15. v(t) = − sin ti + cos tj + C1 , v(0) = j + C1 = i, C1 = i − j, v(t) = (1 − sin t)i + (cos t − 1)j; r(t) = (t + cos t)i + (sin t − t)j + C2 , r(0) = i + C2 = j, C2 = −i + j so r(t) = (t + cos t − 1)i + (sin t − t + 1)j Exercise Set 14.6 514 16. v(t) = ti − e−t j + C1 , v(0) = −j + C1 = 2i + j; C1 = 2i + 2j so v(t) = (t + 2)i + (2 − e−t )j; r(t) = (t2 /2 + 2t)i + (2t + e−t )j + C2 r(0) = j + C2 = i − j, C2 = i − 2j so r(t) = (t2 /2 + 2t + 1)i + (2t + e−t − 2)j 17. v(t) = − cos ti + sin tj + et k + C1 , v(0) = −i + k + C1 = k so C1 = i, v(t) = (1 − cos t)i + sin tj + et k; r(t) = (t − sin t)i − cos tj + et k + C2 , r(0) = −j + k + C2 = −i + k so C2 = −i + j, r(t) = (t − sin t − 1)i + (1 − cos t)j + et k. 1 1 1 j + e−2t k + C1 , v(0) = −j + k + C1 = 3i − j so t+1 2 2 1 1 1 −2t 1 C1 = 3i − k, v(t) = 3i − j+ e k; − 2 t+1 2 2 18. v(t) = − r(t) = 3ti − ln(t + 1)j − 1 −2t 1 e + t k + C2 , 4 2 9 1 r(0) = − k + C2 = 2k so...
View Full Document

Ask a homework question - tutors are online